Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/foods11152251
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Textural Quality and Water Retention of Spiced Beef under Ultrasound-Assisted Sous-Vide Cooking and Its Possible Mechanisms

Abstract: The present study investigated the effects of ultrasound (28 kHz, 60 W at 71 °C for 37 min) combined with sous-vide cooking (at 71 °C for 40, 60, 80, 100, 120 min) on the textural quality, water distribution, and protein characteristics of spiced beef. Results showed that the spiced beef treated with conventional cooking (CT) had the highest cooking loss (41.31%), but the lowest value of shear force (8.13 N), hardness (55.66 N), springiness (3.98 mm), and chewiness (64.36 mJ) compared to ultrasound-assisted so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The WBSF was measured according to the previous method (Wang et al., 2022). The meat samples were drilled using a circular sampler with a diameter of 1.27 cm along the direction parallel to the muscle fibers (avoiding tendons), with a minimum bore length of 2.5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The WBSF was measured according to the previous method (Wang et al., 2022). The meat samples were drilled using a circular sampler with a diameter of 1.27 cm along the direction parallel to the muscle fibers (avoiding tendons), with a minimum bore length of 2.5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The carbonyl content of proteins was determined with a slightly modified method of Wang et al [20] . 10 mM 2,4-dinitrophenyl hydrazine (DNPH) was mixed with 1 mL MP solution (2 mg/mL) at 25℃ for 1 h. The mixture was precipitated with 1 mL 20% trichloroacetic acid (TCA) solution and centrifuged at 12 000 × g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [ 16 ] characterized the effect of processing stage on the physicochemical properties and volatile flavor components of dry-cured donkey leg, and demonstrated that aldehydes, esters, alkanes, and alcohols were more abundant in the final products. Wang et al [ 17 ] demonstrated that ultrasound combined with sous-vide cooking was closely related to the improvements in the textural quality of spiced beef. Wang et al [ 18 ] demonstrated that the treatment of high pressure at 50 °C significantly improved the textural parameters of Chinese traditional pig trotter with soy sauce.…”
mentioning
confidence: 99%